Synthis and Phisical And Chemical; Properties of SiO[2]-B[2]O[3] and SiO[2]-P[2]O[5] Thin Film Systems and Powders; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Malchik A. G. Aleksandra Gennadievna; Litovkin S. V. Sergey Valerievich; Seregin V. I.; Rodionov P. V. Pavel Vadimovich; Kryuchkova S. О. (2016, 2016)
Title screen